Experiences of unemployment, the meaning of wage work: the dilemma of wage work among ex-gold mineworkers in the Free State Goldfields - Sefalafala, Thabang Masilo (My University, 2018)
The thesis explores experiences of unemployment to understand the meaning of wage work. This ethnographic research focuses on the everyday lived experiences of unemployed ex-mineworkers in their local contexts. Through personal narratives of men laid off from the dying Goldfields of the Free State (previously called the Orange Free State (OFS), it aims to explicate the powerful moral effects of wage work in a context of pervasive joblessness. Ex-mineworkers affirmed their commitment to wage work as the only way in which security, respect, pride, and dignity can happen in society. Yet, increasingly, in South Africa and indeed across the world, wage work can no longer fulfil those values and its traditional promise. The findings illuminate how unemployment had a profound impact on ex-mineworkers’ sense of self and their place in their homes and communities. They suffer stigma, diminished sense of masculine confidence and negative self-perceptions. The thesis describes the ways in which unemployment was experienced as economic insecurity, social insecurity, and psychological distress. However, I argue that these impairments are only symptoms of a much deeper problem, that is, they experienced a deep moral unease at being unemployed. These impairments do not produce deleterious effects on the unemployed merely because they cause poverty, social uncertainties, and psychological distress, which of course are important, but because a particular moral regulation has lost hold over individuals. The thesis argues that unemployment produced deleterious effects on the unemployed because it occasioned the abrupt disruption of, and loss of shared collective moral values without the immediate provision of an alternative collective moral order in place of the old. As such, unemployment is experienced as loss. Ex-mineworkers attempted to overcome the three impairments through a combination of livelihood strategies. Strategies included standing by the side of the road (men by the side of the road), collecting scrap metal for recycling and remittances. They often inadequately benefitted (indirectly) from various state grants. The livelihood activities they undertook were seen as humiliating and driven by desperation and they were unable to facilitate and secure sustainable and predictable sources of economic security or new forms of social status and dignity. With the above in mind, ex-mineworkers imagined the positive impact that a Basic Income Grant (BIG) or an unemployment grant would have in reducing the insecurities (economic, social, and psychological) of the unemployed. They framed grants as ‘handouts’ which while reducing insecurities, cannot, ultimately, substitute wage work and the values tied to it. They preferred employment and jobs over non-wage forms of income distribution. But this raises a policy dilemma; What happens when full employment becomes impossible? If job creation fails, how do we explain the continued commitment to wage work as the central medium of what it means to live a productive life? I argue, the answer lies not only with respect to the economic benefits tied to jobs, but rather, a deeper historical sociological factor, which is the moral status of wage work in society. The moral status and commitment to wage work, not only makes wage work the only perceived viable way of attaining livelihoods, a meaningful life, masculine status etc., but it also hegemonically blinds the unemployed, policy makers and analysts to imagine possibilities of decent life outside wage work.
A thesis submitted in fulfilment to the degree of Doctor of Philosophy to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, South Africa, 2018